Bending Test and Simulation of Welded Galvanized Steel Pipes - Mohammed Saber (Tehnički Vjesnik, 2021)
Galvanized pipes have to be either welded together or to other components. In this paper, experimental and finite element (FE) studies were carried out to investigate the behaviour of welded A53 B galvanized pipes subjected to bending loading. Firstly, tensile tests of the pipe material and of the weld metal were carried out. Pieces of the galvanized pipe, each of 300 mm, were welded together using arc welding. A welded pair of pipes was sliced longitudinally and subjected to bending load in two different directions: root-bending and face-bending. FE study was carried out on models of the welded pipes. The obtained results revealed that the pipe material showed non-homogeneity in tensile testing. Moreover, the face-bending strength was two times the root-bending strength. The FE analysis was accurately able to predict the maximum loading the joint can support.